Drug treatment for metastatic breast cancer - E. V. Artamonova (Опухоли женской репродуктивной системы)
The paper describes the basic principles of drug therapy for metastatic breast cancer and considers treatment options for this disease. It also analyzes and details hormonal therapy and chemotherapy regimens and evaluates the efficacy of drugs used in these regimens and their dif- ferent combinations.